VALUASI EKONOMI DENGAN METODE BIAYA PERJALANAN DI OBJEK WISATA BUKIT BAWANG BAKUNG KABUPATEN LAMPUNG BARAT - Zuliardo; Ktut Murniati; Firdasari Firdasari (Lampung University, 2026)
This research aimed to analyze varios key factors that influenced the frequency of tourist visits, and estimate the economic value generated by Bukit Bawang Bakung Tourism through the application of the Travel Cost Method (TCM). The study was located at a tourism area namely Bukit Bawang Bakung in Pekon Negeri Ratu, Batu Brak Subdistrict, West Lampung Regency, Lampung Province. The study site was determined purposively due to its relevance to the research objectives. Data collection was conducted from May to June 2025. The research sample consisted of 76 visitors of Bukit Bawang Bakung tourism area, selected by using a survey-based data collection method. To analize the data, this research employed multiple linear regression to examine the influence of various explanatory variables on visit frequency, alongside the Travel Cost Method to quantify the economic value of the tourism site. The empirical results revealed that travel expenses, travel distance, and visitor income significantly affecedt the number of tourist visits to Bukit Bawang Bakung. In addition, by integrating the estimated consumer surplus per visit with annual visitation levels, the total economic value of Bukit Bawang Bakung Tourism was estimated to reach IDR 37,241,485,397.84 per year, highlighting the substantial economic contribution of this destination. Keywords: economic valuation, tourist visit frequency, travel cost method